Efecto del Transporte de Cerdos de Ceba en la Incidencia de Cerdos Fatigados y Lesionados - Romero, Marlyn Hellen (2017)
The aim of this study was to determine the effect of transport of market-weight pigs on the incidence of fatigued and injured pigs. An observational prospective study was performed to evaluate 18 437 pigs (n=350 batches) that were unloaded at three commercial slaughterhouses in Colombia. The mortality rate was 0.0016% and the incidence of fatigued and injured pigs was 0.02%. Transport time, stocking density, slaughterhouse, batch mixing, type of truck, speed and assistant on the journey were associated with nonambulatory pigs incidence.